Preferential colonization of metastases by oncolytic vaccinia virus strain GLV-1h68 in a human PC-3 prostate cancer model in nude mice. - Ulrike Donat (PLoS ONE, 2012)
Recently, we showed that the oncolytic vaccinia virus GLV-1h68 has a significant therapeutic potential in treating lymph node metastases of human PC-3 prostate carcinoma in tumor xenografts. In this study, underlying mechanisms of the virus-mediated metastases reduction were analyzed. Immunohistochemistry demonstrated that virus-treatment resulted in a drastically decrease of blood and lymph vessels, representing essential routes for PC-3 cell migration, in both tumors and metastases. Thus, GLV-1h68 drastically reduced essential routes for the metastatic spread of PC-3 cells. Furthermore, analysis of viral distribution in GLV-1h68-injected tumor-bearing mice by plaque assays, revealed significantly higher virus titers in metastases compared to solid tumors. To elucidate conditions potentially mediating the preferential viral colonization and eradication of metastases, microenvironmental components of uninfected tumors and metastases were compared by microscopic studies. These analyses revealed that PC-3 lymph node metastases showed increased vascular permeability, higher proliferation status of tumor cells as determined by BrdU- and Ki-67 assays and lesser necrosis of PC-3 cells than solid tumors. Moreover, an increased number of immune cells (MHCII(+)/CD68(+) macrophages, MHCII(+)/CD19(+) B lymphocytes) combined with an up-regulated expression of pro-inflammatory cytokines was observed in metastases in comparison to primary PC-3 tumors. We propose that these microenvironmental components mediated the metastatic tropism of GLV-1h68. Therefore, vaccinia virus-based oncolytic virotherapy might offer a novel treatment of metastatic prostate carcinomas in humans.